A passage on the dynamics of physical-spatial development of Abar city using GIS - Ali Mohammadi; Shahram Amirentakhabi; Azam Mohamadzade (اکولوژی انسانی, 2024)
Uncontrolled urban developments have led to changes in the uncontrolled urban spatial structure. Therefore, informed guidance, principled organization and spatial surveillance are necessary for urban expansion. Therefore, the purpose of this research is to study the process of physical-physical development of Abbar city, to identify the effective factors in physical-physical development in the GIS environment and to analyze them in the geographic information system database, using the AHP model. By preparing information layers such as land availability, topography, rural points, slope, communication network, cemetery, river and entering these layers into the GIS environment and analyzing them in the geographic information system database, using the AHP model. Suitable lands for the future development of the city were identified. The results of the research showed that the master plan of the city has played a major role in the direction of the physical development of the city, and the physical development of the city is coordinated with the expansion of service uses and urban equipment, and these types of uses have a balanced spatial distribution. But it does not match the conventional standards.